God-Unıverse Relatıonshıp In Al-Farabı Accordıng To Huseyin Atay - Öztürk Kocabıyık, Nilüfer (Scientific Journal of Faculty of Theology, 2020)
In this study, we tried to deal with how the God-universe relationship took shape in Farabi’s philosophical system and the nature of creation according to Hüseyin Atay. Atay, who has done important studies in the fields of Philosophy and Kalam, is known for his new approaches and ideas in these areas. Within the framework of the God-universe relationship, it can be said that he tries to reconcile the systems and al-Farabi theologians. Unlike some researchers who have studied on Farabi, Atay shows that the idea of creating from nothing needs to be reconsidered in a different perspective by incorporating it in the philosophical system of philosophers.